2008
DOI: 10.1007/s00134-008-1219-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of epinephrine and norepinephrine in critically ill patients

Abstract: Despite the development of potential drug-related effects with epinephrine, there was no difference in the achievement of a MAP goal between epinephrine and norepinephrine in a heterogenous population of ICU patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
191
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(202 citation statements)
references
References 24 publications
5
191
0
6
Order By: Relevance
“…However, clinical trials do not demonstrate worsening of clinical outcomes. One RCT comparing norepinephrine to epinephrine demonstrated no difference in mortality but an increase in adverse drug-related events with epinephrine [265]. Similarly, a meta-analysis of four randomized trials (n = 540) comparing norepinephrine to epinephrine found no significant difference in mortality (RR 0.96; CI 0.77-1.21; low-quality evidence) (ESM 9) [264].…”
Section: G Vasoactive Medicationsmentioning
confidence: 99%
“…However, clinical trials do not demonstrate worsening of clinical outcomes. One RCT comparing norepinephrine to epinephrine demonstrated no difference in mortality but an increase in adverse drug-related events with epinephrine [265]. Similarly, a meta-analysis of four randomized trials (n = 540) comparing norepinephrine to epinephrine found no significant difference in mortality (RR 0.96; CI 0.77-1.21; low-quality evidence) (ESM 9) [264].…”
Section: G Vasoactive Medicationsmentioning
confidence: 99%
“…Rationale: A prospective, double-blind, randomizedcontrolled trial of norepinephrine versus epinephrine in achieving mean arterial pressure in ICU patients 20 found that epinephrine was associated with the development of significant but transient metabolic effects (tachycardia, lactic acidosis, insulin requirements) that prompted the withdrawal of 18/139 (12.9%) patients from the study by attending clinicians. There was no difference in 28 and 90-day mortality.…”
Section: Statement: Epinephrine Increases Metabolic Abnormalities Commentioning
confidence: 99%
“…There were no significant differences in the treatments received by participants in both groups and once again no difference in mortality. Besides these trials, it is also notable that a randomised clinical trial comparing the use of adrenaline to noradrenaline in critically ill patients demonstrated a significant increase in lactate levels, without any differences in clinical outcomes [7]. This provides further evidence that resuscitation guided by changes in lactate levels is very unlikely to improve mortality.…”
mentioning
confidence: 95%